Pencegahan dini diabetes melitus sebagai ‘Mother of Disease’ pada remaja melaui edukasi kesehatan - Muhamad Ramadhan Salam; Siti Rahmatia; Tika Herawati; Amelia Ramadani; Syarifa Fadhillah; Agis Setiawan; Siti Isdar Rahmayani; Kristina Teniwut; Anggun Anggun; Amelianti Amelianti (Universitas Mataram, 2026)
Diabetes mellitus (DM), one of the most common non-communicable diseases (NCDs) worldwide, is starting to affect children and adolescents. Activities aimed at early prevention of diabetes mellitus among adolescents were conducted at SMAN 1 Sawa, involving 31 students. The initiative began with obtaining permission from the school and preparing educational materials focused on diabetes prevention, including risk factors, how to prevent it, complications of diabetes mellitus, and a healthy lifestyle. The event took place in November 2024 at the SMAN 1 Sawa Hall, starting with an opening by a school representative, followed by the administration of a pretest to the students. The comprehensive health education session lasted from 09:00 to 11:00 WITA. The evaluation phase of the activity involved distributing posttest questionnaires to students to assess the effectiveness of the health education. The post-education evaluation showed a significant improvement in students' knowledge, with scores increasing from 39.8% before the session to 71.7% afterward. The activity underscored the need for continuous education and support from families and schools to improve adherence to healthy dietary practices and prevent diabetes-related complications.